Metal assemblages in Late Bronze Age Greek mainland funerary contexts: an investigation for their identification as functional metal hoards - Kypraiou, Filia (2023)
Bronze Age metal hoards in Europe have been extensively studied with a focus on their intended purpose and the reason/s behind their survival in the archaeological record, but definite answers cannot be given. A similar issue is also encountered in the Late Bronze Age Aegean more specifically and debate exists whether the increase in metal hoarding in the final centuries of the Late Bronze Age in the Aegean is the result of a copper/bronze shortage or abundance. Both in the Aegean and wider Europe, most scholars studying metal hoards are focusing on those from non-funerary contexts, dismissing the idea that metal assemblages in tombs interpreted as grave goods may also be hoards and which may have even been intended to be retrieved in the face of poverty and/or a metal shortage. This possibility has only been briefly looked at by Greek scholars and archaeologists and so the purpose of this thesis is to study further this possibility using the case studies of the Late Bronze Age tholos tombs at Kokla and Nichoria and the chamber tombs 2, 7 and 10 at Dendra in the Peloponnese. The research questions that are answered in this project are: can the content and context of selected non-funerary metal hoards provide any clues for their identification? Are there content similarities between funerary metal assemblages and non-funerary metal hoards? Could the funerary metal assemblages be retrieved from the tomb and put back into circulation? Can a metal shortage be responsible for the increase in metal hoarding on the late LBA Greek mainland? Through the study of metal assemblages from these tombs that are not clearly associated with any burials and their comparison to selected non-funerary hoards, also from the Late Bronze Age Greek mainland, this thesis shows that there are significant similarities between the two in the content and to some extent even the context. It concludes that these funerary metal assemblages can reasonably be considered as retrievable hoards to be used in times of need. The availability of scrap metal, the good-quality bronzework and the Linear B tablets from Pylos are argued to indicate that there was not a copper/bronze shortage on the mainland in the final centuries of the Late Bronze Age. Therefore, this research also concludes that the rise in metal hoarding during that time probably does not relate to an actual copper/bronze shortage.